Synthesis methods of gold nanoparticles for Localized Surface Plasmon Resonance (LSPR) sensor applications - Samsuri, ND; Mukhtar, WM; Rashid, ARA; Dasuki, KA; Yussuf, AARHA (E D P Sciences, 2024)
Indexed by SCOPUS/WOS